Masalah Keislaman Umat Islam Sebagai Tantangan Bagi Peningkatan Mutu Pendidikan Agama Islam - Syamsu Yusuf LN. (STAI Siliwangi Bandung, 2016)
The religious life of Muslims actually can have an impact on the formation of a noble character of every believer, and the creation of atmosphere of harmonious society, peaceful, and prosperous, according to the mission God sent the Prophet Muhammad as rahmatan lil'alamiin. But in reality, there are some Muslims who were their attitudes and behavior (moral) is not reliable with the values ​​of religion. This occurs, probably due to lack of their understanding against the real values ​​of Islam, and the massive temptation of lust hubbuddunya wakarohiyatul maut, or because the mindset is already contaminated (poisoned) by values, opinions, or ideology other odds with the values ​​of Islam who exemplified the Prophet. Under these conditions, if there is no improvement (recovery) of Muslims in earnest will bear a negative stigma for Muslims themselves, which ultimately Islam would lose the opportunity to actively engage constructively in the process of determining the policies and strategic positions in national and state life. One solution to improve the condition of the people, and preparing a new pious generation is to improve the quality of religious education, both within the family, school, and community.